Do physicians with academic affiliation have lower burnout and higher career-related satisfaction? - Chu Zhuang; Xiaochu Hu; Michael J. Dill (BMC Medical Education, 2022)
Abstract Background Physicians report increasing burnout and declining career-related satisfaction, negatively impacting physician well-being and patient care quality. For physicians with academic affiliations, these issues can directly affect future generations of physicians. Previous research on burnout and satisfaction has focused on factors like work hours, gender, race, specialty, and work setting. We seek to contribute to the literature by examining these associations while controlling for demographic, family, and work-related characteristics. Furthermore, we aim to determine any differential effects of faculty rank. Methods We analyzed data on practicing physicians in the U.S. from the Association of American Medical College’s (AAMC) 2019 National Sample Survey of Physicians (NSSP,) which includes variables adapted from the Maslach Burnout Inventory. We used ordinal logistic regressions to explore associations between academic affiliation and burnout. We conducted a factor analysis to consolidate satisfaction measures, then examined their relationship with academic affiliation using multivariate linear regressions. All regression analyses controlled for physicians’ individual, family, and work characteristics. Results Among respondents (n = 6,000), 40% were affiliated with academic institutions. Physicians with academic affiliations had lower odds than their non-affiliated peers for feeling emotional exhaustion every day (Odds Ratio [OR] 0.87; 95% CI: 0.79–0.96; P < .001) and reported greater career-related satisfaction (0.10–0.14, SE, 0.03, 0.02; P < .001). The odds of feeling burnt out every day were higher for associate professors, (OR 1.57; 95% CI: 1.22–2.04; P < .001) assistant professors, (OR 1.64; 95% CI: 1.28–2.11; P < .001), and instructors (OR 1.72; 95% CI, 1.29–2.29; P < .001), relative to full professors. Conclusions Our findings contribute to the literature on burnout and career satisfaction by exploring their association with academic affiliation and examining how they vary among different faculty ranks. An academic affiliation may be an essential factor in keeping physicians’ burnout levels lower and career satisfaction higher. It also suggests that policies addressing physician well-being are not “one size fits all” and should consider factors such as academic affiliation, faculty rank and career stage, gender identity, the diversity of available professional opportunities, and institutional and social supports. For instance, department chairs and administrators in medical institutions could protect physicians’ time for academic activities like teaching to help keep burnout lower and career satisfaction higher.